2003
DOI: 10.1123/pes.15.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a 3-Day Physical Activity Recall Instrument in Female Youth

Abstract: The purpose of this study was to examine the validity of the 3-Day Physical Activity Recall (3DPAR) self-report instrument in a sample of eighth and ninth grade girls (n = 70, 54.3% white, 37.1% African American). Criterion measures of physical activity were derived using the CSA 7164 accelerometer. Participants wore a CSA monitor for 7 consecutive days and completed the self-report physical activity recall for the last 3 of those days. Self-reported total METs, 30-min blocks of MVPA, and 30-min blocks of VPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
3
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(230 citation statements)
references
References 21 publications
5
217
3
4
Order By: Relevance
“…A moderate correlation (r 5 0?36) was also found when comparing time spent in MVPA between both methods. Similar results with activity monitors have been reported for other subjective instruments used to assess PA in adolescents (25)(26)(27) . The Bland-Altman plot indicates that the Bouchard AD tended to overestimate MVPA in adolescents compared with the activity monitor and that the mean difference in time spent in MVPA between both methods was significant (P 5 0?027).…”
Section: Discussionsupporting
confidence: 85%
“…A moderate correlation (r 5 0?36) was also found when comparing time spent in MVPA between both methods. Similar results with activity monitors have been reported for other subjective instruments used to assess PA in adolescents (25)(26)(27) . The Bland-Altman plot indicates that the Bouchard AD tended to overestimate MVPA in adolescents compared with the activity monitor and that the mean difference in time spent in MVPA between both methods was significant (P 5 0?027).…”
Section: Discussionsupporting
confidence: 85%
“…A análise da reprodutibilidade foi efetuada em 50 instrumentos e da validade em 71. Ou seja, em alguns instrumentos foi analisada apenas a reprodutibilidade (n = 8) 36,37,38,39,40,41,42,43 , em outros a validade (n = 29) 16,18,21,25,28,30,31,32,33,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60 .…”
Section: Resultsunclassified
“…Identificaram-se 52 instrumentos diferentes (42 questionários, 6 diários e 4 entrevistas estruturadas), mas apenas 11 haviam sido testados mais de uma vez 16,18,20,21,22,24,25,26,29,30,31,33,35,36,37,39,41,44,46,49,52,54,55,58,59,60,61,62,63,64,65,66,67 . A maioria destes instrumentos (33/52) 19,20,21,22,23,24,25,27,28,32,35,38,40,41,46,47,50,51,53,…”
Section: Resultsunclassified
“…Girls also completed a revised Three Day Physical Activity Recall (3DPAR) (Pate et al, 2003;McMurray et al, 2004) which indicated where they did PA (i.e., home/neighborhood, school, other outdoor public area, other, and community facilities). Community facilities included parks, playgrounds, recreation centers, churches, dance studios, and fields or gyms.…”
Section: Use Of Community Facilitiesmentioning
confidence: 99%